2018
DOI: 10.1055/a-0677-9608
|View full text |Cite
|
Sign up to set email alerts
|

Assoziationen zwischen der Rumpfkraft und judospezifischen Anriss-Leistungen von Judoka

Abstract: Zusammenfassung Hintergrund Eine gut ausgeprägte Rumpfstabilität ist eine wichtige Voraussetzung für die Mobilität der oberen und unteren Extremitäten während des sportlichen Bewegungsvollzugs. Vor diesem Hintergrund könnte die Rumpfkraft ein leistungsdeterminierender Faktor bei der Ausführung judospezifischer Bewegungen darstellen. Das Ziel der vorliegenden Studie war es, statistische Zusammenhänge zwischen der Rumpfkraft und kinetischen Parametern bei Anriss-Bewegungen von Judoka zu untersuchen. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…The torso is a body region frequently used in judo techniques. The strength development in the torso is associated with specific performance parameters in judo players [ 25 ]. Our findings indicate that fat accumulation in the trunk region has a negative impact on performance in the SJFT, as well as in the other evaluated tests (CMJ, SJ, FPU, and PPU).…”
Section: Discussionmentioning
confidence: 99%
“…The torso is a body region frequently used in judo techniques. The strength development in the torso is associated with specific performance parameters in judo players [ 25 ]. Our findings indicate that fat accumulation in the trunk region has a negative impact on performance in the SJFT, as well as in the other evaluated tests (CMJ, SJ, FPU, and PPU).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between maximal force and rate of force production on judo performance has been widely investigated, providing evidence that the development of these physical attributes may transfer to judo techniques (e.g., throwing: harai-goshi [hip], sasaetsurikomi-ashi [foot], and morote-seoi-nage [shoulder]). For example, research addressing the relationship between trunk muscle strength and judo-specific pulling performances in judokas using a specially designed system mimicking the judo technique morote-seoi-nage showed that the trunk flexors accounted for 69% of the mechanical work, therefore advising judokas to develop trunk muscle strength to support dynamic pulling movements (28). Reducing the number and severity of injuries sustained by judoka and accelerating return to competition from injury is of interest given the high prevalence of injuries in judo, particularly in areas exposed to more significant stress and impacts during specific techniques and combat (4,33,54).…”
Section: Issues and Improvementsmentioning
confidence: 99%